2020
DOI: 10.1063/5.0010664
|View full text |Cite
|
Sign up to set email alerts
|

Screw dislocation that converts p-type GaN to n-type: Microscopic study on Mg condensation and leakage current in p–n diodes

Abstract: Recent experiments suggest that Mg condensation at threading dislocations induces current leakage, leading to degradation of GaN-based power devices. To investigate this, we perform first-principles total-energy electronic-structure calculations for various Mg and dislocation complexes. We find that threading screw dislocations (TSDs) indeed attract Mg impurities, and that the electronic levels in the energy gap induced by the dislocations are elevated toward the conduction band as the Mg impurity approaches t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 38 publications
0
20
0
Order By: Relevance
“…The TDs have deleterious effects on the performance and lifetime of GaN-based devices through mechanisms such as carrier scattering, 9,10 carrier trapping via nonradiative recombination (NRR), [11][12][13][14][15][16] and paths for leakage current. [17][18][19][20][21][22] These different mechanisms are connected by the fact that dislocations act as one-dimensional (1D) charged defects that introduce electronic states into the energy gap. 14,[22][23][24] It is well accepted that the negative effects of dislocations on devices are strongly dependent on their Burgers vector and are susceptible to other dislocation characteristics, such as their line direction, 20 core structure, 20,22,[25][26][27] impurity gettering, 14,22 and surface morphology.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The TDs have deleterious effects on the performance and lifetime of GaN-based devices through mechanisms such as carrier scattering, 9,10 carrier trapping via nonradiative recombination (NRR), [11][12][13][14][15][16] and paths for leakage current. [17][18][19][20][21][22] These different mechanisms are connected by the fact that dislocations act as one-dimensional (1D) charged defects that introduce electronic states into the energy gap. 14,[22][23][24] It is well accepted that the negative effects of dislocations on devices are strongly dependent on their Burgers vector and are susceptible to other dislocation characteristics, such as their line direction, 20 core structure, 20,22,[25][26][27] impurity gettering, 14,22 and surface morphology.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19][20][21][22] These different mechanisms are connected by the fact that dislocations act as one-dimensional (1D) charged defects that introduce electronic states into the energy gap. 14,[22][23][24] It is well accepted that the negative effects of dislocations on devices are strongly dependent on their Burgers vector and are susceptible to other dislocation characteristics, such as their line direction, 20 core structure, 20,22,[25][26][27] impurity gettering, 14,22 and surface morphology. 21 However, there are large discrepancies in the literature regarding the relationship between the dislocation behavior and their structural properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…19,[37][38][39][40] As an example, Nakano et al reported that a stable atomic core structure of screw dislocations grown under a N-rich environment had no deep states in the bandgap, while a core structure formed under a Ga-rich condition created deep states. 19,37 Belabass et al showed that screw dislocations having non-stoichiometric closed-core configurations with N atoms removed from the core had a metallic-like electronic structure that could provide highly conductive pathways in GaN crystals. 38 Based on these studies, the majority of the b=1c screw TDs in the present work had closed-core structures with no deep states inducing current leakage, while a very few b=1c screw TDs, such as that associated with pit #M2, had an atomically different closed-core structure with harmful deep states.…”
Section: Discussionmentioning
confidence: 99%
“…The inconsistent leakage behavior of TDs observed in these studies strongly suggests that the effects of the TDs on GaN-based power devices are sensitive to the growth conditions 13 and thereby not solely determined by the type of TD. Specifically, factors such as the Burgers vector 5 , core structure 14 , inclination direction 15 , 16 and strain field of the dislocations 17 , as well as point defects interacting with the TDs 4 , 10 , 17 – 19 , may influence the electrical characteristics of these defects. Unfortunately, few studies have examined the detailed relationships between such structural characteristics and the electrical properties of TDs, primarily because of challenges related to quantitative electrical measurements of individual TDs.…”
Section: Introductionmentioning
confidence: 99%